Spatiotemporal Dynamics of Meta Population Models with Application in Law - Walo, R. O.; Ndondo, A. M.; Bonane, S. Mushi (Discontinuity, Nonlinearity, and Complexity, 2026)
The paper deals with a spatiotemporal dynamics study of criminality city-by-city in attempt to model mechanisms which give rise to synchronisation outbreak of crimes in different cities and villages. The study gives sharp relations between social and penal pressions.